Sahelanthropus tchadensis nicknamed “Toumaï”: The earliest known Hominin - (:unkn) unknown (My University, 2020)
Since 1994 the Mission Paléoanthropologique Franco-Tchadienne (MPFT) is digging in northern Chad (Djurab desert), where it first unearthed a new australopithecine, nicknamed “Abel” (3.5 My) the first ever found West of the Rift Valley. In 2002, MPFT described the new earliest known Hominini (the Human family sister group of Panini, the chimps) Sahelanthropus tchadensis, nicknamed Toumaï (7 My), bipedal by its cranial anatomy while sedimentology and associated faunal assemblage (more than 100 fossil species) point out a mosaic landscape with lakes, wetlands, patches of forest, wooded islets, wooded savannah and grasslands. S. tchadensis displays a unique combination of primitive and derived characters that clearly show that it is not related to chimpanzees or gorillas, but to hominins, and temporally close to the last common ancestor between chimpanzees and humans. Then these earliest hominins were not restricted to Eastern and Austral Africa but were rather living in a wider geographic region, including Sahelian and Central tropical Africa.
Keywords: African Research